LEFT LUNG AGENESIS IN AN ADULT – A RARE ANOMALY - Wahinuddin Sulaiman; Ramani Subramaniam (Asian Journal of Medicine & Health Sciences, 2020)
Pulmonary agenesis is a rare congenital anomaly and only a few cases are reported in the literature. Adult cases present with a heterogeneous spectrum of manifestations and radiological findings. Historically, the diagnosis was made during autopsy, but with modern imaging technology, the diagnosis can be confidently made based on radiological findings. We present a 72 year old lady with left lung agenesis, diagnosed at the age of 40 years old. This is the first case to be reported in Malaysia.